PEMANFAATAN WEBSITE SIMPLEDRIVE BERBASIS CLOUD DATABASE UNTUK ARSIP DIGITAL GUNA MENGHINDARI RESIKO KEHILANGAN DATA - Astuti, Indah Fitri; Rismayanti, Rismayanti; Putri Ananda, Kania; Maulidiah, Nurmedina; Evalyn Lolongan, Agditha (Fakultas Teknologi Informasi dan Industri Unisbank, 2024)
The community engagement activity in Selili Subdistrict, Samarinda City, aims to provide education on the importance of digital data archiving and the risks of data loss. Through training sessions on using a scanner application and SimpleDrive, the objective is to empower the community to effectively manage digital archives, avoid data loss, and enhance efficiency in data retrieval. The activity plan encompasses meetings with local subdistrict authorities and community leaders, the development of educational materials, the implementation of training sessions, and the provision of a concise guide on file management and data backup. Evaluation and surveys are conducted to assess the effectiveness of the program. The anticipated outcome is to deliver significant benefits and foster the practical application of technology in everyday life.